KOMUNIKASI HORIZONTAL SEBAGAI DETERMINAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN DAN KINERJA EKONOMI LEMBAGA PEMERINTAH DAERAH - Ujang Sanusi (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of horizontal communication on decision-making effectiveness at the UPTD of National Education, Buay Pemuka Peliung Subdistrict, OKU Timur Regency. The research employed a quantitative associative method involving all UPTD employees as respondents. Data were collected through observation, interviews, documentation, and questionnaires using a Likert scale. Data analysis utilized Pearson’s correlation coefficient and t-test at a 5% significance level. The findings reveal a strong and positive relationship between horizontal communication and decision-making effectiveness, with a correlation coefficient of 0.681 and a determination contribution of 46.38%. This indicates that effective peer-level communication enhances the quality and accuracy of decision-making in public organizations. The study highlights the strategic role of horizontal communication as a coordination and collaboration mechanism within local educational bureaucracy and as a foundation for participatory, adaptive, and accountable governance